Contribution of Hand Muscle Strength and Waist Muscle Strength to Hand Slams of Greco Roman Style Wrestling Athletes in Bengkulu Province in 2024 - Saputra, Bahrony Elwansyah (Indonesian Journal of Sport, Health and Physical Education Science, 2024)
This study aims to determine the contribution of hand muscle strength and waist muscle strength to the ability of scientific hand slams. The formulation of the problem in this study is how much is the contribution of hand muscle strength and waist muscle strength together to the ability of hand slams in wrestling? This research was conducted at the Bengkulu Province PPLP wrestling gym. The research method used is quantitative research, the research sample amounted to 12 Bengkulu Province wrestling athletes who were taken with total sampling technique. The contribution of hand muscle strength to the ability of hand slams is 77.44% and the contribution of waist muscle strength to the ability of hand slams is 81%. The data results of rcount = 0.88 > rtable = 0.576 then Ho is rejected and Ha is accepted, meaning that there is a relationship between the contribution of hand muscle strength and waist muscle strength together to the ability of hand slams in wrestling. The contribution of hand muscle strength and waist muscle strength to the ability of hand slams is K = r² x 100% = (0.88)² x 100% = 77.44%. So it can be concluded that the positive contribution between hand muscle strength and waist muscle strength to the ability of hand slams is 77.44%.